Development of Google Sites Featuring Jombang Legends as a Teaching Media for Indonesian Language - Trisnawati, Any; Subrata, Heru; Istiq'faroh, Nurul; Mariana, Neni; Rachmadyanti , Putri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This development research aims to examine the feasibility of the Google Sites based instructional media as a learning tool for narrating the Legend of Jombang. The Google Sites learning media can be accessed through each student’s device. Through validation tests involving media experts, content experts, and peer reviewers, as well as individual, small group, and large group trials, this Google Sites learning media is expected to serve as an effective educational innovation for 21st century learning. This study employs a Research and Development (R&D) approach using the ADDIE development model. The research subjects were fifth grade students at elementary schools. The results of the media expert validation showed an average feasibility score of 91.6%, while the material expert validation obtained an average of 90.9%. Peer evaluation yielded an average score of 90%, followed by individual trials with an average of 85%, small group trials with 88.5%, and large group trials with 91.16%. Based on the results of the validation and trials, the Google Sites media developed is very feasible and relevant in today's digital era, serving as an implementation of the Merdeka Curriculum.